Surgical treatment of the complications of gastric and duodenal peptic ulcer indications - Protzel, C. A. (1956)
In this paper we shall deal only with the surgical indications in the treatment of complications of peptic ulcer disease, gastric and duodenal. First, we state that the ulcer is a very common disease, and whose primary treatment should be medical, but its complications should be treated surgically. The incidence of this condition is such that, in reality, is of serious character, and sin not exaggerated if we place between social conditions and the mechanization century.